A Multilevel Model of Entrepreneurship Education and Entrepreneurial Intention: Opportunity Recognition as a Mediator and Entrepreneurial Learning as a Moderator - Hou, Fei; Su, Yu; Qi, Mingde; Chen, Jun; Tang, Jiayun (Frontiers in Psychology, 2022)
Highlighting the implications of entrepreneurship education, this study examines the effects of entrepreneurship education in predicting the entrepreneurial intention of university students. The study also explores the mediating role of opportunity recognition and the moderating role of entrepreneurial learning in this process. To test our multilevel-moderated mediation model, based on a dataset containing 1,150 university students from 55 universities in the Guangdong-Hong Kong-Macao Greater Bay Area of China, hierarchical linear modeling is utilized to test the research hypotheses. The findings reveal that entrepreneurship education can promote the entrepreneurial intention of students through opportunity recognition. Furthermore, entrepreneurial learning plays a moderating role in the link between entrepreneurship education and opportunity recognition. Implications for the design and delivery of entrepreneurship education are discussed.